2013
DOI: 10.1007/s11356-013-1472-9
|View full text |Cite
|
Sign up to set email alerts
|

The function of digestive enzymes on Cu, Zn, and Pb release from soil in in vitro digestion tests

Abstract: The bioaccessibility of soil heavy metals is the solubility of soil heavy metals in synthetic human digestive juice, which is usually determined using in vitro digestion test. To reveal the effects of digestive enzymes on soil heavy metals bioaccessibility, three representative in vitro digestion tests, Simple Bioaccessibility Extraction Test (SBET), Physiologically Based Extraction Test (PBET), and Simple Gastrointestinal Extraction Test (SGET), were chosen. The bioaccessibility of soil Cu, Zn, and Pb in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The process of digestion was proven to diminish the antioxidant activity of the samples in all studied types of digestion protocols. The obtained data is interesting and remains consistent with the previously published results for other plant species [12]. Based on these observations, the process of digestion seems to decompose phenolic constituents in the foods, leading to a marked decrease in its antioxidant potential.…”
supporting
confidence: 91%
“…The process of digestion was proven to diminish the antioxidant activity of the samples in all studied types of digestion protocols. The obtained data is interesting and remains consistent with the previously published results for other plant species [12]. Based on these observations, the process of digestion seems to decompose phenolic constituents in the foods, leading to a marked decrease in its antioxidant potential.…”
supporting
confidence: 91%
“…In contrast, the proportion of intestinal extraction (pH = 7.0) of PBET (range: 0.93-10.5%; average: 4.55%) was relatively smaller than those in the gastric phase extraction of SBET and PBET (pH = 1.5 and 2.5, respectively). These results suggest that Zn is more easily dissolved in an acidic condition, which is in consistence with the findings of a previous work [65].…”
Section: Environmental Risk Assessmentsupporting
confidence: 92%
“…As the pH rises, Cu appears to be stabilized in solution by complexation with available organic ligands from the dust matrix, and with other reagents used in the extraction procedure such as the malate ion and anions of bile acids [ 19 ]. An intermethod comparison study by Li et al [ 41 ] found that the digestive enzymes used in the PBET gastric phase kept soil Cu in solution during the intestinal phase, despite the increase in pH. Their study showed that the solubility of soil Cu in the intestinal phase of PBET remained constant or was even promoted as a result of the presence of the digestive enzymes, whereas the solubility of soil Zn and Pb was pH dependent [ 41 ].…”
Section: Discussionmentioning
confidence: 99%